Patients with acephalic spermatozoa syndrome linked to novel TSGA10/PMFBP1 variants have favorable pregnancy outcomes from intracytoplasmic sperm injection. Issue 3 (21st June 2021) - Liu, Gang; Xing, Xiaowei; Zhang, Huan; Zhu, Wenbing; Lin, Ge; Lu, Guangxiu; Li, Weina
Abstract: Acephalic spermatozoa syndrome is a rare form of teratozoospermia characterized by headless spermatozoa. Previous studies have found that variants in SUN5, PMFBP1, TSGA10, BRDT, and SPATC1L are associated with this phenotype. Many researchers have suggested that variants in TSGA10 without a proximal centriole might influence early embryonic development. This retrospective cohort study included 12 infertile men with severe acephalic spermatozoa in China. We identified six heterozygous variants and four homozygous variants in TSGA10 / PMFBP1 in seven patients by whole‐exome sequencing (WES). Acephalic spermatozoa defects due to different genetic variations may affect only spermatozoa morphology but do not reduce the chances of fertilization, affect embryo quality at early stages or impair intracytoplasmic sperm injection (ICSI) outcomes. Patients with TSGA10 / PMFBP1 variations were all expected to have good prognoses with ICSI. Abstract :